BAcTrace, a tool for retrograde tracing of neuronal circuits in Drosophila. - Cachero, S.; Gkantia, M.; Bates, A.S.; Frechter, S.; Blackie, L.; McCarthy, A.; Sutcliffe, B.; Strano, A.; Aso, Y.; Jefferis, G.S.X.E. (Nature Methods, 2020)
Animal behavior is encoded in neuronal circuits in the brain. To elucidate the function of these circuits, it is necessary to identify, record from and manipulate networks of connected neurons. Here we present BAcTrace (Botulinum-Activated Tracer), a genetically encoded, retrograde, transsynaptic labeling system. BAcTrace is based on Clostridium botulinum neurotoxin A, Botox, which we engineered to travel retrogradely between neurons to activate an otherwise silent transcription factor. We validated BAcTrace at three neuronal connections in the Drosophila olfactory system. We show that BAcTrace-mediated labeling allows electrophysiological recording of connected neurons. Finally, in a challenging circuit with highly divergent connections, BAcTrace correctly identified 12 of 16 connections that were previously observed by electron microscopy.